Physiological and anatomical characteristics of leaves of two clones of guarana - Gonçalves, José Francisco de Carvalho; Júnior, Ulysses Moreira dos Santos; Silva, José Ferreira da; Arruda, Murilo Rodrigues de; Bonates, Luiz Carlos de Matos; Fernandes, Andreia Varmes (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to analyze gas exchange, photosynthetic characteristics, photochemical efficiency of photosystem II and anatomical characteristics of young plant leaves of two guarana (Paullinia cupana) clones (BRS-CG372RC and BRS-CG611RL) growing under open field. The variables of gas exchange and fluorescence of chlorophyll a were evaluated in mature leaves. The values of photosynthesis and transpiration found for BRS-CG372RC were 27% greater and 80% lesser than values found for BRS-CG611RL, respectively. The values of stomatal conductance found for the clones BRS-CG372RC and BRS-CG611RL were in the order of 224 and 614 mmol mm-2 s-1, respectively. The values of photorespiration, rate of carboxylation and rate electron transport were greater in BRS-CG372RC. The clone BRS-CG372RC exhibited stomatal density 26% greater than BRS-CG611RL. However, the area of ostiolar opening was 42% greater in BRS-CG611RL. The values of the water use efficiency in BRS-CG372RC were 134% greater than in BRS-CG611RL. High stomatal density and low stomatal conductance can be important characteristics in the selection of the clones with a good ability to assimilate carbon and optimize the use of water.